ENGLISH COMMUNICATION AND EMPLOYABILITY SKILLS IN STARTUP COMPANY AMONG GRADUATES: CASE STUDY OF A UNIVERSITY IN JAKARTA IN POST COVID-19 PANDEMIC - Wulandari Dwi Putri; Ena Bhattacharyya; Silih Warni (ELLTER Journal, 2022)
The global workforce of the 21st century needs not only young and skilled human capital capable of technical skills, but also academic skills in English as a priority. This study employed a quantitative approach with the survey design. The aim was to investigate how importance of English communication skills and Employability skills of Jakarta graduates post covid-19 in the workplace. The data showed that the questionnaire with total 20 items was sent to 101 Human Resource and Senior Manager in Jakarta, Indonesia, the highest selected options Human Resource and Senior Manager chose was very important and important. This data showed that the Human Resource and Senior Manager stated that the communication skills perceived as important for graduates. The questionnaire with total 40 items was sent to 203 graduates who have graduated in the last five years and works in StartUp company in Jakarta, Indonesia, the highest selected answers from graduates was Strongly Agree and Agree with total mean score 7.01. This data showed that graduates agreed that English communication have big impact for their employability skills. Based on the findings, this research revealing that the English communication is important for Graduates at the StartUp company in Jakarta. Human Resources and the graduates who are working in StartUp company, who already filled out surveys approval that the English communication has an influence on their ability.